Situation analysis of street based female sex workers: violence experiences of women in Nepal: A Study of Kathmandu Valley. - Karki,Rita Devi (2015)
ABSTRACT: Commercial sex is hidden and a debating burning issue taken as risk profession in the sense of reproductive health perspective, stigmatized and illegal status in the country. Street based sex workers are supposed to be vulnerable group because of professional hazards associated with occurrence of extreme form of violence. This study explores the current working situation, reproductive health condition, perception of their profession and legal status and different violent situations among the street based female sex workers who were interviewed through snow-ball sampling techniques with 110 FSWs in Kathmandu Valley. This is a non experimental research based on cross-sectional design using both quantitative and qualitative data collection techniques and presented with descriptive approach and thematic arrangement. The study found economic factor (69.1%) was one of the main factors for starting sex work. There were 49.1 percent illiterate. Most of the FSWs (89.1%) were migrated from different parts of the country covering different castes. The median age of respondent was 37 within the range 16-58 years. Most of the respondents' (73.6%) age when starting sex trade was below 30 years. The age range was 13-54 years which clearly shows that this profession was the involuntary (60%).(...If I were alone, I would take the decision of suicide at that time... this way I was compelled to adopt sex trade just for food for me and my son...) and unknowingly involved (29.1%) rather than voluntary (10.9%). The living condition of FSWs was very poor because some (4.5%) spent their whole time lonely in the street. The minimum money taken from a client was below Rs. 100 (...I felt very lucky myself when I got up to Rs.100 and became happy but I only rarely was able to save this money from street boys...) and maximum was above Rs 2100. Hotel/restaurant was the major (40.0%) destination place for the sex. Total 71 participants experienced STIs and 74 FSWs did not regularly use condom. Chronic STIs, unwanted pregnancy, violence and group sex from clients are the major risk outcomes. (...Client compelled me to drink more alcohol and made unconscious....I became pregnant four times and also suffered from STIs.) Violence was common among the sex workers. 87.3 percent FSWs experienced physical abuses, 90 percent suffered from sexual misbehave, and about 96 percent got little payment. Police, clients, husband and relatives were involved more in this type of violence in comparison to other perpetrators where unhealthy and unsafe sexual practices and other types of violence and their consequences made them life very complex.